2014
DOI: 10.1111/bph.12770
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐(1–7) induces cerebral ischaemic tolerance by promoting brain angiogenesis in a Mas/eNOS‐dependent pathway

Abstract: BACKGROUND AND PURPOSEAs a newer component of the renin-angiotensin system, angiotensin-(1-7) [Ang-(1-7) ] has been shown to facilitate angiogenesis and protect against ischaemic damage in peripheral tissues. However, the role of Ang-(1-7) in brain angiogenesis remains unclear. The aim of this study was to investigate whether Ang-(1-7) could promote angiogenesis in brain, thus inducing tolerance against focal cerebral ischaemia. EXPERIMENTAL APPROACHMale Sprague-Dawley rats were i.c.v. infused with Ang-(1-7), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 45 publications
7
85
0
Order By: Relevance
“…These effects are not accompanied with changes of arterial BP [23,25], indicating that outcomes of Ang-(1-7) are likely independent of changes in BP. Consistent with the prior findings, in the current report, ICV injection of Ang-(1-7) fails to significantly alter BP in non-diabetic SHR animals; however, it lowers SBP in diabetic SHR animals.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…These effects are not accompanied with changes of arterial BP [23,25], indicating that outcomes of Ang-(1-7) are likely independent of changes in BP. Consistent with the prior findings, in the current report, ICV injection of Ang-(1-7) fails to significantly alter BP in non-diabetic SHR animals; however, it lowers SBP in diabetic SHR animals.…”
Section: Discussionmentioning
confidence: 88%
“…Prior studies have shown that central chronic administration of Ang-(1-7) increases survival of stroke-prone SHR rats, and improves cerebral blood flow, neurological deficits and brain ischemic tolerance evoked by middle carotid artery occlusion in rats [23,25]. These effects are not accompanied with changes of arterial BP [23,25], indicating that outcomes of Ang-(1-7) are likely independent of changes in BP.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…When the production of NO • is obstructed, tumor angiogenesis is suppressed. [57, 58] Cytokine interleukin-33 (IL-33), a regulator of vasculature, was also shown to promote proliferation, migration, angiogenesis and vascular permeability by stimulating endothelial NO • generation through the ST2/TRAF6-Akt-eNOS signaling pathway. [59] In addition, the reduction of NO • formation achieved by knockdown eNOS using siRNA markedly decreased endothelial cells migration in shear stress; however, a supplement of external NO • donor led to a 2-fold recovery in angiogenesis (Fig.…”
Section: Angiogenesismentioning
confidence: 99%
“…The ACE2/Ang-(1-7)/Mas pathway has been highlighted as a promising target for induction of stroke neuroprotection 4 , and has proven efficacy in reducing infarct size and improving neurological function in preclinical models of ischemic 5-11 and hemorrhagic stroke 12 . Stroke neuroprotection has been demonstrated in both young 5, 6 and aged 10 animals, and methods for activating the axis have included direct intracerebroventricular administration of Ang-(1-7) 5, 7, 11 , delivery of ACE2-primed endothelial progenitor cells 8 , and neuronal ACE2 overexpression 9 . Pharmacological activation of this axis has recently become more feasible with the identification of diminazene aceturate, trade name Berenil®, as an activator of ACE2 13 .…”
Section: Introductionmentioning
confidence: 99%